Two new species of the genus Homogryllacris (Orthoptera: Gryllacrididae) with the first description of the female of Homogryllacris foveolis Zhang, Pang & Bian, 2023 from China - Duan, Yanhao; Su, Jie; Cai, Fanduo; Shi, Fuming (Zootaxa, 2024)
In the paper, two new species of the genus Homogryllacris Liu, 2007 are described from China, i.e. Homogryllacris breviprocera Duan, Su & Shi sp. nov. and Homogryllacris xizangensis Duan, Su & Shi sp. nov. The female of Homogryllacris foveolis Zhang, Pang & Bian, 2023 is described for the first time. In addition, images illustrating the morphology of the two new species and the female of H. foveolis Zhang, Pang & Bian, 2023 are provided.